The relative contribution of non-timber forest products, agriculture and off-farm sources of income to rural households in Koloni and Guquka, Eastern Cape - Mtati, Nosiseko (Rhodes University, Faculty of Science, Department of Environmental Science, 2015)
[Partial abstract]: This study was carried out to determine the contribution of non-timber forest products (NTFPs) to household total income, other livelihood sectors were also examined simultaneously. The contribution of agriculture involved livestock and crop production. Wages and government grants were other livelihood sectors that were looked into. This study was important in determining the change in livelihood strategies in the last decade and to quantify the NTFPs used at the two sites. It was carried out in Guquka and Koloni, both part of the central Eastern Cape. Information on direct use value of the NTFPs used, the quantities and local price; crop production outputs and inputs and the costs. Data were collected via a questionnaire.
Keywords: Informal sector (Economics) -- South Africa -- Eastern Cape; Rural development -- South Africa -- Eastern Cape; Rural poor -- South Africa -- Eastern Cape; Households -- Economic aspects -- South Africa -- Eastern Cape; Forest products -- South Africa -- Eastern Cape; Non-timber forest products -- South Africa -- Eastern Cape; Agriculture -- Economic aspects -- South Africa -- Eastern Cape; Natural resources -- South Africa -- Eastern Cape; Income -- South Africa -- Eastern Cape